2013
DOI: 10.1039/c2mt20151h
|View full text |Cite
|
Sign up to set email alerts
|

Localization of copper and copper transporters in the human brain

Abstract: Disturbances in brain copper result in rare and severe neurological disorders and may play a role in the pathogenesis and progression of multiple neurodegenerative diseases. Our current understanding of mammalian brain copper transport is based on model systems outside the central nervous system and no data are available regarding copper transport systems in the human brain. To address this deficit, we quantified regional copper concentrations and examined the distribution and cellular localization of the copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 68 publications
4
117
1
1
Order By: Relevance
“…substantia nigra accumulates twice as much Cu as the surrounding brain regions (Fig. 7) [122]. Copper in the brain is mainly associated with holoenzymes, transporters and chaperones, and homeostatic proteins [123].…”
Section: Copper Zinc and Related Biomolecules In The Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…substantia nigra accumulates twice as much Cu as the surrounding brain regions (Fig. 7) [122]. Copper in the brain is mainly associated with holoenzymes, transporters and chaperones, and homeostatic proteins [123].…”
Section: Copper Zinc and Related Biomolecules In The Brainmentioning
confidence: 99%
“…Copper in the brain is mainly associated with holoenzymes, transporters and chaperones, and homeostatic proteins [123]. Cu-containing enzymes are mainly involved in cell respiration, iron metabolism, ROS defense mechanisms, and significantly, the synthesis of neurotransmitters (dopamine [124]) and neuron myelinization [122].…”
Section: Copper Zinc and Related Biomolecules In The Brainmentioning
confidence: 99%
“…Moreover, astrocytes have a higher level of ATP7A than neurons (Figure 2A), revealing a powerful capability of copper regulation in astrocytes to protect neurons from copper toxicity and deficiency (Scheiber et al 2012;Scheiber & Dringen 2013). The immunocytochemistry analysis displayed the typical pattern of perinuclear ATP7A distribution under the low-copper conditions (Figure 3), in which ATP7A fulfilled its main function to deliver copper for incorporation into copper-dependent enzymes (Iwase et al 1996;Davies et al 2013;Scheiber & Dringen 2013). ATP7A immunoreactivity was absent from neuron axons and dendrites ( Figure 3C), while it was ample in mature primary hippocampal neurons (Schlief et al 2005) and olfactory receptor neurons (Meskini et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…ATP7A is widely expressed throughout the brain, but shows significant differences in different regions of the brain such as greater levels in the brain barriers and cerebellum than in other brain regions (Qian et al 1998;Choi & Zheng 2009;Davies et al 2013). In addition, research on immunohistochemistry and hybridization in situ showed that expression of ATP7A is regulated spatially and temporally by nervous system development.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates the metabolism of copper in the brain. Brain concentrations range from 3.1 to 5.1 mg/g wet weight [11,12]. Within the brain, the distribution of copper is heterogeneous.…”
Section: +mentioning
confidence: 99%